AN ANALYSIS OF SONGS ABOUT MOTHER BY NGUYEN VAN TY FROM SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE - Hang, Ta Thi Thu (VNU Journal of Foreign Studies; Vol 37 No 4, 2021)
This paper explores experiential meaning realized in transitivity resource and interpersonal meaning realized in the mood and modality resources of two songs about mother by Nguyen Van Ty. The discussion of the experiential and interpersonal meaning explored will enable the researcher to have a better understanding of the image of mother depicted in the two songs. The theoretical framework employed for analysis is Systemic Functional Linguistics. The data for analysis is all clause simplexes collected from the two songs. The findings show that material process is mostly used in both songs and followed by mental, relational and behavioural processes. There are no verbal and existential processes found in both songs. In terms of interpersonal meaning, there is a very high frequency of declarative clauses and a very small number of interrogative and exclamative clauses. Although the occurrence of modality is very humble, it is deployed in both songs. It is recommended that the two songs can be used as an effective source for students who take an interest in studying the Vietnamese language from Systemic Functional Linguistics view.